Assessment of long-term energy efficiency improvement and greenhouse gas emissions mitigation options for the cement industry. (1st March 2019) - Talaei, Alireza; Pier, David; Iyer, Aishwarya V.; Ahiduzzaman, Md; Kumar, Amit
Abstract: The cement industry is responsible for between 5% and 9% of global greenhouse gas (GHG) emissions. The increasing trend of GHG emissions from cement sector highlights the importance of GHG mitigation in this industry. In the current study, bottom-up energy modelling and scenario analyses were used to assess long-term GHG mitigation potential in the cement industry. The developed comprehensive, data-intensive, and technology-rich model is flexible and can be used to study the GHG mitigation potential in different regions. For the case study of Canada, a reference scenario along with 20 GHG emissions' reduction scenarios were developed in the Long-range Energy Alternative Planning (LEAP) model. For each scenario, cumulative energy saving and GHG reduction potential were analyzed. Furthermore, the net present value, cost of saved energy, and carbon were calculated to assess the economic performance of different scenarios. Carbon abatement cost curves were also developed using the GHG mitigation potential and the cost of implementing different energy efficiency options. Overall, compared to the reference scenario, the cumulative GHG mitigation potentials in the Canadian cement sector are 27 and 59 million tonnes CO2 eq. by the years 2030 and 2050, respectively. More than 70% of the emissions' reduction is achievable with negative cost. Highlights: A bottom-up and technology-rich model is developed for the cement industry. Energy consumption demand tree is used to analyze the energy intense sub-processes. 20 scenarios are developed to assess the long-term energy saving and GHG mitigation. Carbon abatement cost curves are developed to rank energy saving options.